Stagnations- und Deflationstheorien Studien zur Entwicklung der ökonomischen Theorie - Caspari, Volker (Schriften des Vereins für Socialpolitik, 2021)
»Theories of Economic Stagnation and Deflation« Originally, the idea of secular stagnation was proposed by the American economist Alvin Hansen in the late 1930s. In 2013, Larry Summers took up this idea in a speech to the IMF. Classical economists such as D. Ricardo and J. St. Mill have also dealt with this topic in detail. This volume presents comparisons between older and more recent approaches explaining economic stagnation and deflation.